Intravenous infusion of 5-hydroxytryptophan to mid-lactation Holstein cows transiently affects milk production and circulating amino acid concentrations - Virginia L. Pszczolkowski; Meghan K. Connelly; August Hoppman; Amara D. Benn; Jimena Laporta; Laura L. Hernandez; Sebastian I. Arriola Apelo (Journal of Dairy Science, 2024)
ABSTRACT: In dairy cows, the lactating mammary glands synthesize serotonin, which acts in an autocrine-paracrine manner in the glands and is secreted into the periphery. Serotonin signaling during lactation modulates nutrient metabolism in peripheral tissues such as adipose and liver. We hypothesized that the elevation of circulating serotonin during lactation would increase nutrient partitioning to the mammary glands, thereby promoting milk production. Our objective was to elevate circulating serotonin via intravenous infusion of the serotonin precursor 5-hydroxytryptophan (5-HTP) to determine its effects on mammary supply and extraction efficiency of AA, and milk components production. Twenty-two multiparous mid-lactation Holstein cows were intravenously infused with 5-HTP (1 mg/kg body weight) or saline, in a crossover design with two 21-d periods. Treatments were infused via jugular catheters for 1 h/d, on d 1 to 3, 8 to 10, and 15 to 17 of each period, to maintain consistent elevation of peripheral serotonin throughout the period. Milk and blood samples were collected in the last 96 h of each period. Whole-blood serotonin concentration was elevated above saline control for 96 h after the last 5-HTP infusion. Dry matter intake was decreased for cows receiving 5-HTP, and on average they lost body weight over the 21-d period, in contrast to saline cows who gained body weight. Milk production and milk protein yield were lower in cows receiving 5-HTP during the 3 infusion days, but both recovered to saline cow yields in the days after. Although milk fat yield exhibited a day-by-treatment interaction, no significant difference occurred on any given day. Milk urea nitrogen concentration was lower in 5-HTP cows on the days following the end of infusions, but not different from saline cows on infusion days. Meanwhile, plasma urea nitrogen was not affected by 5-HTP infusion. Circulating concentrations of AA were overall transiently decreased by 5-HTP, with concentrations mostly returning to baseline within 7 h after the end of 5-HTP infusion. Mammary extraction efficiency of AA was unaffected by 5-HTP infusion. Overall, both lactation performance and circulating AA were transiently reduced in cows infused with 5-HTP, despite sustained elevation of circulating serotonin concentration.